Damage and repair of aerospace composite materials - Lu, Y. Charles (SAE International, 2020)
Damage and repair of aerospace composite materials reports the latest developments on the detection and repair of composite structures from the perspective of ten SAE technical papers, especially chosen for this book.
Keywords: Aerospace engineering.; Composite materials.; Airplanes -- Maintenance and repair.; Airframes -- Maintenance and repair.; elektronické knihy; electronic books